2020
DOI: 10.1007/s00330-020-07372-w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and prognostic indicators of symptomatic air embolism after percutaneous transthoracic lung biopsy: a systematic review and pooled analysis

Abstract: Objectives To determine the incidence, risk factors, and prognostic indicators of symptomatic air embolism after percutaneous transthoracic lung biopsy (PTLB) by conducting a systematic review and pooled analysis. Methods We searched the EMBASE and OVID-MEDLINE databases to identify studies that dealt with air embolism after PTLB and had extractable outcomes. The incidence of air embolism was pooled using a random effects model, and the causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 106 publications
0
27
0
2
Order By: Relevance
“…Strokes as a complication are very rare and most are air emboli, with a risk of 0.06–0.08% [ 3 ]. Suspicion for cerebral air embolism is warranted when patients present with focal neurologic changes following lung biopsy procedures and supported by visualization of air intracranially on MRI or CT [ 4 , 5 ]. Additionally, if indeed a patient experienced an air embolism, a CT scan would detect even the smallest amounts of air due to air’s negative 1000 Hounsfield units, which creates a large contrast with brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Strokes as a complication are very rare and most are air emboli, with a risk of 0.06–0.08% [ 3 ]. Suspicion for cerebral air embolism is warranted when patients present with focal neurologic changes following lung biopsy procedures and supported by visualization of air intracranially on MRI or CT [ 4 , 5 ]. Additionally, if indeed a patient experienced an air embolism, a CT scan would detect even the smallest amounts of air due to air’s negative 1000 Hounsfield units, which creates a large contrast with brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published data by Lee et al showed that pooled incidence of symptomatic air embolism after TTNB was 0.08% (95% CI, 0.048–0.128%), and one-third of cases had sequelae or died ( 23 ). The finding was in concordance with our result, where 0.12% (3/2,556) of our study cohort had symptomatic air emboli.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge is that systemic air embolisms after CT-TTNB are extremely rare, and the symptoms vary from completely asymptomatic to acute fatal with cardiac arrest as the first symptom. 4 , 5 Studies have systematically and for research purposes performed thoracic CT scans after CT-TTNB to identify systemic air embolisms and the literature report an incidence of approximately 0.08%–4.8%. 5 , 6 Risk factors for systemic air embolisms are described as cough during the procedure and high-pressure ventilation.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Studies have systematically and for research purposes performed thoracic CT scans after CT-TTNB to identify systemic air embolisms and the literature report an incidence of approximately 0.08%–4.8%. 5 , 6 Risk factors for systemic air embolisms are described as cough during the procedure and high-pressure ventilation. The prospective and retrospective cohorts, gathered in systematic reviews and meta-analyses, aim to explore incidences and causal relationships (risk factors) of systemic air embolisms as described, but rarely focus on occurrence of rare events and how they are clinically handled.…”
Section: Introductionmentioning
confidence: 99%